Cyber Security Threats to Iran and its Countermeasures: Defensive and Offensive Cyber Strategies - Syed Qandil Abbas; Hareem Fatima (National University of Modern Languages (NUML), Islamabad, 2024)
Iran's convoluted geopolitical status, its centrality to locale-specific wars, plus the shifting balance of the global order make cyber security a key issue worldwide in addition to traditional security challenges. Iran is an appealing target for cyber enemies due to its numerous security vulnerabilities, which include ransomware infection, scams, as well as complicated malware. Iran has taken a flexible stance, via collaboration, authorized, and intellectual tactics to counter these concerns. Forming cyber security teams, utilizing the latest innovations, and hiring competent employees are all examples of efforts in cyber defense. Legislative structures are essential for bringing criminals before the law and discouraging unlawful behaviour, but the dynamic nature of cyber threats makes it difficult to update rules. The goal is to keep information security and safety measures under check. The identification and mitigation of cyber dangers necessitate collaboration with various nations, global organizations, and corporations. Iran's cyberspace involvement shapes societal sentiment and upholds the will of the people, with both advantageous and hazardous repercussions. To bolster its application and balance its powerful adversaries, it employs cyber assaults in conjunction with conventional asymmetrical combat strategies. What is Iran's main cyber security concerns and challenges, and how is Iran addressing as well as tackling them, is the question that this study aims to answer.